2021
DOI: 10.1111/geb.13372
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of tree species and human disturbance in determining the macrofungal diversity in Europe

Abstract: AimKnowledge concerning species distribution is important for biodiversity conservation and environmental management. Fungi form a large and diverse group of species and play a key role in nutrient cycling and carbon storage. However, our understanding of fungal diversity and distribution remains limited, particularly at large spatial scales. Here, we predicted the diversity and distribution of ectomycorrhizal and saprotrophic macrofungi at relatively fine spatial resolution at a continental scale and examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…Due to the exceptional ecological importance of macrofungi, research on their synecology, biogeography, and conservation status is becoming more and more plentiful [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Nevertheless, papers related to mycological research on forest habitats most often deal with the issue of only certain ecological groups of macrofungi: exclusively mycorrhizal [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] or lignicolous [ 8 , 19 , 20 , 21 , 22 , 23 ]. In contrast, studies covering the overall diversity of all ecological and taxonomic groups of macrofungi are considerably less frequent [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the exceptional ecological importance of macrofungi, research on their synecology, biogeography, and conservation status is becoming more and more plentiful [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Nevertheless, papers related to mycological research on forest habitats most often deal with the issue of only certain ecological groups of macrofungi: exclusively mycorrhizal [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] or lignicolous [ 8 , 19 , 20 , 21 , 22 , 23 ]. In contrast, studies covering the overall diversity of all ecological and taxonomic groups of macrofungi are considerably less frequent [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In total, we compiled a dataset with 1845 macrofungal species and 878,978 records for final use in our model (Figure 1). More details of the dataset can be found in the study of Yu, Wang, et al (2021). All statistical analyses reported in this study, including the preprocessing of fungi data and predictor variables, were conducted in R (R Core Team, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…As outlined above, plants provide carbon to macrofungi (Bässler et al, 2010; Krah et al, 2018; Watkinson et al, 2015), and many local studies have found that macrofungi composition and diversity are affected by the tree species composition and diversity (Jaroszewicz et al, 2021; Schmit et al, 2005; Zhang et al, 2010). A recent study also revealed that the dominant tree species play a crucial role in determining the diversity and distribution of macrofungi at the continental scale (Yu, Wang, et al, 2021). Given that tree species can form mutualistic relationships with macrofungi and provide them with resources, potential changes in tree species diversity and distribution under ongoing climate change (Lenoir et al, 2008; Vitasse et al, 2021) are likely to further influence related macrofungal diversity and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…To address our hypotheses, we compiled data on annual mean temperature and temperature seasonality. From previous studies, we know that mean and seasonal precipitation, soil organic carbon, nitrogen deposition and tree diversity correlate with the spatial distribution of fungal species (Andrew et al 2018, Yu et al 2021. To account for possible offset effects, we considered these variables as covariates.…”
Section: Environmental Datamentioning
confidence: 99%